Long non-coding RNA NEAT1 promotes bladder progression through regulating miR-410 mediated HMGB1 - Guang Shan (Biomedicine & Pharmacotherapy, 2020)
LncRNA NEAT1 is reported as a crucial oncogene in multiple cancers. But, its biological role in bladder cancer is barely understood. Therefore, we concentrated on the function and role of NEAT1 in bladder cancer. Firstly, NEAT1 expression in bladder cancer cells was determined and it was displayed NEAT1 was significant elevated. NEAT1 was knockdown and overexpressed in T24 and J82 cells. Then it was indicated that NEAT1 silence greatly inhibited bladder cancer cell proliferation with an increased ratio of apoptotic cells and severe cell cycle arrest. Overexpression of NEAT1 exhibited a reversed process in bladder cancer cells. Additionally, in vivo experiments were employed using establishment of nude mice models. NEAT1 knockdown inhibited bladder cancer growth while increase of NEAT1 promoted bladder cancer development in vivo. By employing the bioinformatics analysis, we speculated that miR-410 was as a downstream target of NEAT1. Then, the targeting association between them was proved in our research and we implicated miR-410 was dramatically restrained in bladder cancer cells. Meanwhile, it was exhibited that miR-410 was negatively regulated by NEAT1. Apart from these, HMGB1 was speculated as a downstream target of miR-410. Dual-luciferase reporter assay was used to prove the correlation between miR-410 and HMGB1. Up-regulation of miR-410 restrained HMGB1 levels and NEAT1 can regulate HMGB1 level via sponging miR-410. To sum up, we implied NEAT1/miR-410/HMGB1 axis participated in bladder cancer.